The Presupposition Triggers in Thesis Abstract - Eka Surya Fitriani (ITScience (Information Technology and Science), 2021)
Abstract drew a summary of the author's writing in a thesis or others publication research. It was outlined some essential points to ease the reader toward the whole investigation. Regarding the presupposition, this study purposed to see the triggers used in students' thesis' abstract and the way authors presuppose in their abstract writing from its motivation in the form of linguistic features. The finding showed that the existential type is mainly used in the abstracts by qualitative research. In the condition of the definite noun phrase and some possessive form, the findings stated the existence of the background knowledge having within the truth value found by the thesis writers. A presupposition was known as a general property of language use has been defined as those taken-for-granted and shared implicit claims inherent in the explicit meaning of a text. The abstract writers formulated and summarized the main point of their research, and thus it provided much potential information and knowledge from the thesis.